Study on layout optimization of sewage outfalls: a case study of wastewater treatment plants in Xiamen - Cui Wang; Zhouhua Guo; Qingsheng Li; Jing Fang (Scientific Reports, 2021)
Abstract In order to protect the offshore environment and strengthen the comprehensive rectification of sewage outfalls, an evaluation method of regional sewage outfalls by combining the marine numerical simulation and comprehensive evaluation technology was constructed, considering the marine environmental capacity and the ecological impact of sewage discharge from outfalls on the marine eco-environment sensitive areas. Then the layout rationality of each outfall was evaluated and the discharge scale was optimized with a case study of existing sewage outfalls in Xiamen. The results show that, the comprehensive evaluation score of Yundang outfall was 3 points in 2025, evaluated as the outfall with irrational layout. In 2035, the comprehensive evaluation scores of Fenglin and Dalipu outfalls were 3 and 2 points respectively, evaluated as the outfall with irrational discharge scale. It is suggested to control the scale of expansion or increase the reclaimed water reuse rate in Jimei and Gaoqi Wastewater Treatment Plants. This method has enriched the evaluation system for layout optimization of sewage outfalls, providing scientific supports for comprehensive improvement of sewage outfalls and marine environmental management.